Design development and characterization of an advanced smart window for building indoor comfort and energy reduction - Ming, Yang (2024)
This study explored the development and analysis of a novel façade system integrating Thermotropic Parallel Slat Transparent Insulation Material (TT PS-TIM) within the double-glazed window cavities, aimed at enhancing a building’s indoor environment and energy efficiency. The methodology commenced with a comprehensive literature review, guiding the selection and preparation of thermotropic (TT) materials in the laboratory, developing the thermotropic slices and then integrating the developed slices into traditional double glazing to form the thermotropic parallel slices transparent insulation materials prototype window system. To have a better understanding of the improvement of indoor comfort and energy-saving potential by applying TT PS-TIM window system, a comprehensive research process was undertaken numerically and experimentally which included the optical characterization of TT materials, thermal performance of the TTP PS-TIM system and daylight/energy performance of a building equipped with TT PS-TIM window system. To be more specific, focusing on optimal optical properties and thermal responsiveness, PNIPAm and HPC TT materials were selected and tested. Subsequently, TT slats were crafted and developed by encapsulating TT hydrogels within TIM slices for further TT PS-TIM system development. The overall optical performance such as transmittance, absorptance of the system was numerically studied by Ray-tracing technique based on the experimental assessment of the optical properties of TT slats. These results were imported into an innovatively constructed CFD model which coupled general heat transfer with solar radiation impact to investigate the dynamic thermal performance and transition process of the TT PS-TIM. The results indicated that, compared with traditional double-glazing (DG) systems, TT PS-TIM showcased superior thermal performance, evidenced by over a 20% reduction in heat gain/loss on summer and winter days. After that, the numerical state control strategy of TT PS-TIM was developed based on the CFD results for subsequent evaluations of energy efficiency and daylight optimization and was evaluated by dynamic outdoor experiments. Concluding the study, this research embarked on predicting the annual energy savings and daylight comfort potential of an office space augmented with TT PS-TIM. Compared with the traditional DG system, higher UDI and reduced DGP were performed by an office applied with TT PS-TIM and 38% maximum energy saving could be found.